2017
DOI: 10.17844/jphpi.v20i1.16553
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Seaweed Padina australis and Eucheuma cottonii as Sunscreen Raw Materials

Abstract: Seaweed is one of the main commodity which spread throughout Indonesian waters. Seaweed contains bioactive compounds which can serve as a defense form ultraviolet radiation. The purpose of this study was to obtain chemical composition, phytochemical compounds, vitamin E, and antioxidant activity of extract P. australis and E. cottonii. Chemical composition of P. australis moisture 87.25%; ash 2.34%; protein 1.05%, fat 0.58%; and carbohydrates 8.78% while E. cottonii moisture 76.15%; ash 5.62%; protein 2.32%; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
3
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 7 publications
0
14
3
10
Order By: Relevance
“…The water content of P. australis from Kelapa Lima coastal waters, Kupang Bay, was 11.21%, and it is different from that reported by Fitrya 20 , only 6.4%, and Maharany et al 7 , 87.25%. This difference could be influenced by light intensity and temperature at the drying process.…”
Section: Antibacterial Activity Of P Australiscontrasting
confidence: 67%
See 2 more Smart Citations
“…The water content of P. australis from Kelapa Lima coastal waters, Kupang Bay, was 11.21%, and it is different from that reported by Fitrya 20 , only 6.4%, and Maharany et al 7 , 87.25%. This difference could be influenced by light intensity and temperature at the drying process.…”
Section: Antibacterial Activity Of P Australiscontrasting
confidence: 67%
“…17 These differences could result from dissimilarity in harvest age and weather condition at the rearing period. 7 Furthermore, carbohydrate content in P. australis was higher than in Tidung island, Kupang Bay, only 8.78% 7 and in Souttheast Coast of India, 14.73% 18 , but lower than carbohydrate content in P. gymnospora from Sabah Malaysia, 84.54% 19 and from Tamilnadu, India, 118.14% 16 , and than that in P. minor found in Pahuwato waters, Gorontalo, 41.88 %. 5 The interspecific difference in carbohydrate content reflects that nutrients of macroalgae could be affected by species and habitat.…”
Section: Antibacterial Activity Of P Australismentioning
confidence: 82%
See 1 more Smart Citation
“…[20] However, flavonoids, alkaloids, saponins, terpenes, tannins, phenol, and cardiac glycosides are absent in aqueous extract of P. australis. This is in contrast with the study of Maharany et al which showed the presence of flavonoids, tannins, and saponins in methanolic extract of P. australis [21].…”
Section: Discussioncontrasting
confidence: 99%
“…Ekstrak pigmen karotenoid H. discoidea mempunyai nilai IC50 = 99,65 ppm yang menunjukkan bahwa aktivitas antioksidan yang kuat (Agusti 2015). Aktivitas antioksidan makroalga tersebut telah banyak diaplikasikan, di antaranya untuk bahan kosmetik berupa tabir surya (Luthfana et al 2017;Maharany et al 2017;Yanuarti et al 2017).…”
Section: Pendahuluanunclassified